Ideophonic verb compounds in Archi - Gilles Authier (Linguistic Typology at the Crossroads, 2024)
Archi is a one-village language (1,000 speakers) belonging to the Lezgic branch of East Caucasian. It has a large and productive class of compound verbs combining a light verb and ‘coverbs’ of nominal, adjectival, verbal or unknown origin. It stands out among its closest relatives in the way it has created, under the influence of Lak, a large class of compounds using the verb bos ‘say’. We consider all coverbs used with bos and its allomorphs to be ideophones and propose a semantic classification of all ideophonic verbal compounds: sound and speech verbs, verbs of non-auditory sensations, ingestion, movement, and effortful activities. All primary data were extracted with partial paradigms and some examples from Chumakina et al.’s Archi online dictionary. Their phonotactic shapes, not substantially different from other parts of speech, are examined, as well as borrowings and specific ‘children’s speech’ ideophones.